2022
DOI: 10.1002/mrm.29519
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of transient nuclear Overhauser effect imaging in brain at 7 T

Abstract: The nuclear Overhauser effect (NOE) quantification from the steady-state NOE imaging suffers from multiple confounding non-NOE-specific sources, including direct saturation, magnetization transfer, and relevant chemical exchange species, and is affected by B 0 and B 1 + inhomogeneities. The B 0 -dependent and B 1 + -dependent data needed for deconvolving these confounding effects would increase the scan time substantially, leading to other issues such as patient tolerability. Here, we demonstrate the feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Therefore, multifaceted correction techniques that combine postprocessing and pad usage and, even in the future, pTx, and artificial intelligence should be considered. Consideration should also be given to using dielectric pads and other methods to correct for the same B1+$$ {\mathrm{B}}_1^{+} $$ inhomogeneities present in similar sequences at 7 T such as creatine CEST 33 and transient NOE 34 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multifaceted correction techniques that combine postprocessing and pad usage and, even in the future, pTx, and artificial intelligence should be considered. Consideration should also be given to using dielectric pads and other methods to correct for the same B1+$$ {\mathrm{B}}_1^{+} $$ inhomogeneities present in similar sequences at 7 T such as creatine CEST 33 and transient NOE 34 …”
Section: Discussionmentioning
confidence: 99%
“…One contained deionized water and the other contained 100 mM creatine in DPBS, each had a pH of 7.05 and were scanned at room temperature. The same parameters were used as in previous work 27 .…”
Section: Methodsmentioning
confidence: 99%
“…Patients with high-grade tumors (World Health Organization grade IV) have shown to have reduced rNOE signals in the tumor region due to a degradation of protein content in the brain. 7 Recently, another study has shown the feasibility of measuring transient NOE from the lipids of human brains in vivo at 7 T. 29 Mehrabian et al 30 and Regnery et al 31 demonstrated that rNOE can characterize tumor aggressiveness and identify early progressors even before beginning the treatment. Regnery et al 31 and Meissner et al 32 showed that rNOE-CEST can be used as a biomarker to predict early progression after therapy of CRT in glioblastoma, discriminating between responders and nonresponders.…”
Section: Introductionmentioning
confidence: 99%